Highly sensitive optical thermometers based on unconventional thermometric coupled levels of Tm3+ following a Boltzmann-type distribution in oxyfluoride glass ceramics. (15th October 2019) - Fu, Yuting; Zhao, Lijuan; Guo, Yuao; Yu, Hua
Abstract : Two highly-sensitive innovative coupled levels of 3 F2, 3 / 1 D2 and 3 F2, 3 / 1 G4 governed by a Boltzmann-type distribution in Tm 3+ /Yb 3+ co-doped β-PbF2 GCs were proposed. Abstract : Oxyfluoride glass ceramics (GCs) containing β-PbF2 nanocrystals (NCs) doped with Tm 3+ and Yb 3+ were synthesized by a conventional melt-quenching method and a subsequent glass crystallization route. In β-PbF2 :Tm 3+ /Yb 3+ GCs, Tm 3+ /Yb 3+ is surrounded by fluoride with a low phonon energy, ensuring its intense emissions at 362 ( 1 D2 → 3 H6 ), 450 ( 1 D2 → 3 F4 ), 478 ( 1 G4 → 3 H6 ), 648 ( 1 G4 → 3 F4 ), 700 ( 3 F2, 3 → 3 H6 ) and 800 ( 3 H4 → 3 H6 ) nm excited by 976 nm laser. Furthermore, temperature-dependent upconversion luminescence (UCL) behaviors of β-PbF2 :Tm 3+ /Yb 3+ GCs were systematically investigated to explore the thermometric performance with the assistance of the fluorescence intensity ratio (FIR) method by employing conventional TCELs of 3 F2, 3 / 3 H4 following a Boltzmann distribution and two unconventional coupled levels of 3 F2, 3 / 1 D2 and 3 F2, 3 / 1 G4 governed by a Boltzmann-type distribution. Impressively, the relative sensitivity ( S r ) of 3 F2, 3 / 1 D2 states ( I 700nm / I 362nm ), 3 F2, 3 / 1 G4 states ( I 700nm / I 478nm ), and 3 F2, 3 / 3 H4 states ( I 700nm / I 800nm ) was obtained in this work as values of 1.30% K −1, 1.38% K −1, and 0.87% K −1, respectively. Compared with the conventional TCELs of 3 F2, 3 / 3 H4, the two unconventional coupled levels of 3 F2, 3 / 1 D2 and 3 F2, 3 / 1 G4 present preferable properties as temperature probes enabling optical ratiometric thermometers. The research in this work provides an important advance in exploring other innovative FIR methods for optical thermometers to enable an intense and precise probing signal and detect temperature accurately.